ANALYSIS OF THE APPLICABILITY OF SOME RISK ASSESSMENT MODELS ASSOCIATED WITH EXPOSURE TO RADON FOR EVALUATION OF EFFECTIVENESS OF RADON MITIGATION ACTIONS IN SCHOOLS - D. V. Kononenko (Радиационная гигиена)
The paper presents the results of risk assessment from exposure to radon before and after radon mitigation actions in school. Twofold reduction of radon EEC (from 231 to 109.6 Bq/m3) in the long term can lead to decrease of lifetime attributable risk by 2.2–2.4% for the entire population (depending on the standard population used), 2.7% for men, 1.2% for women. These results were obtained using «FCZ» model. Models «EPA-2003» and «Wismut-2006» were not sensitive enough for use in such tasks.